A new simulation estimator of system reliability. (1994) - Ross, Sheldon M.
Abstract : A basic identity is proven and applied to obtain new simulation estimators concerning (a) system reliability, (b) a multi-valued system. We show that the variance of this new estimator is often of the order α 2 when the usual raw estimator has variance of the order α and α is small. We also indicate how this estimator can be combined with standard variance reduction techniques of antithetic variables, stratified sampling and importance sampling.